Methodological developments in administrative data linkage for cross cutting policy relevant research: Working towards a sustainable data pipeline - Emma Turner; Jen Hampton; Rachel Huck; Clare Melson; Jason Powell-Bavester; Alissa Goodman; George Ploubidis; Robin Flaig; Andy Boyd (International Journal of Population Data Science, 2023)
Objectives Develop administrative linkages within a national Trusted Research Environment (TRE) that hosts Longitudinal Population Study (LPS) data for over 20 LPS. We will describe the methodological development carried out to enable linkage to administrative datasets. These linked administrative data will support research for public good, informing policy and practice.